The Polycystic Ovary Syndrome Current Concepts on Pathogenesis and Clinical Care - Azziz, Ricardo (Endocrine Updates ;, 2007)
Polycystic ovary syndrome (PCOS) is the single most common endocrinologic abnormality of women, affecting approximately 1 in 10-to 15 women of reproductive age. It is also the most frequent cause of oligo-ovulatory infertility. PCOS patients demonstrate androgenic symptoms including hirsutism, alopecia, and acne. Furthermore, patients with PCOS are at significant risk for developing diabetes, hypertension, dyslipidemia, and possibly cardiovascular disease. It is estimated that the healthcare cost exceeds four billion dollars annually in the United States alone, not even accounting for the significant negative effect this disorder has on quality of life. Patients with PCOS are seen by a variety of specialists, depending on needs, including reproductive, medical, and pediatric endocrinologists; gynecologists; general internists; and dermatologists. This text reviews the latest concepts in the pathophysiology, diagnosis, and treatment of the this pervasive and significant disorder, a clear and focused manner. ******************************************************************************* In this concise volume, Dr. Azziz has integrated current clinical knowledge with principles of fundamental genetics and cell biology of polycystic ovary syndrome - a commonly encountered clinical entity.This book will assist clinicians treating this serious and often distressing disorder afflicting so many women in terms of quality of life,fertility and systemic wellbeing.The chapters also provide useful insights for researchers studying mechanisms for pathogenesis of the disorder,and those unraveling novel therapeutic approaches. Ultimately,women with this metabolic and reproductive disorder will benefit from the knowledge which this group of expert authors bring to publication in this text. Shlomo Melmed, M.D. Series Editor Endocrine Updates.